Comparison Performance of 3-Level and 5-Level Cascaded H-Bridge Multilevel Inverter of DTC of Induction Machine - Nair, Ravin; Jidin , Auzani; Othman, Md Nazri; JOPRI, MOHD HATTA; Manap, Mustafa (2013)
Development of electrical vehicle (EV) and hybrid electrical vehicle (HEV) gives many opportunities and challenges in power electronic drive, especially in the development of traction motor drive that requires advanced power electronic inverter. Multilevel inverter was first proposed by Nabae in early 1980. The general structure of the multilevel inverter is to synthesis a sinusoidal voltage out of several levels of dc voltages. This paper shows comparison between the 3-Level Cascaded H-Bridge Multilevel Inverter and 5 -Level Cascaded H-Bridge Multilevel Inverter. It is found that by using 5-level Cascaded H-Bridge Multilevel Inverter (CHMI) can reduce torque and flux ripples compare to 3-Level CHMI and hence can improve DTC performances.